The effect of blood transfusion on compensatory reserve: A prospective clinical trial. Issue 1 (July 2017) - Benov, Avi; Yaslowitz, Ori; Hakim, Tal; Amir-Keret, Rotem; Nadler, Roy; Brand, Anat; Glassberg, Elon; Yitzhak, Avi; Convertino, Victor A.; Paran, Haim
Abstract : BACKGROUND: Bleeding activates the body's compensatory mechanisms, causing changes in vital signs to appear late in the course of progressive blood loss. These vital signs are maintained even when up to 30% to 40% of blood volume is lost. Laboratory tests such as hemoglobin, hematocrit, lactate, and base deficit levels do not change during acute phase of bleeding. The compensatory reserve measurement (CRM) represents a new paradigm that measures the total of all physiological compensatory mechanisms, using noninvasive photoplethysmography to read changes in arterial waveforms. This study compared CRM to traditional vital signs and laboratory tests in actively bleeding patients. METHODS: Study patients had gastrointestinal bleeding and required red blood cell (RBC) transfusion (n = 31). Control group patients had similar demographic and medical backgrounds. They were undergoing minor surgical procedures and not expected to receive RBC transfusion. Vital signs, mean arterial pressure, pulse pressure, hemoglobin and hematocrit levels, and CRM were recorded before and after RBC transfusion or the appropriate time interval for the control group. Receiver operator characteristic curves were plotted and areas under the curves (AUCs) were compared. RESULTS: CRM increased 10.5% after RBC transfusion, from 0.77 to 0.85 ( p < 0.005). Hemoglobin level increased 22.4% after RBC transfusion from 7.3 to 8.7 ( p < 0.005). Systolic and diastolic blood pressure, mean arterial pressure, pulse pressure, and heart rate did change significantly. The AUC for CRM as a single measurement for predicting hemorrhage at admission was 0.79, systolic blood pressure was 0.62, for heart rate was 0.60, and pulse pressure was 0.36. CONCLUSIONS: This study demonstrated that CRM is more sensitive to changes in blood volume than traditional vital signs are and could be used to monitor and assess resuscitation of actively bleeding patients. LEVEL OF EVIDENCE: Care management, level II.